Hypertension Management among Hypertensive Patients in Al-Thawra Hospital, Sana’a City, Yemen: A Cross-Sectional Analysis - Al-Akhali, Khaled; Mahyuob, Abdullah; Al-Ghobabi, Yousef (Journal of Pharmacy Practice and Community Medicine, 2026)
Background: Hypertension remains a leading cause of cardiovascular morbidity in low resource settings, yet data on real-world management practices in conflict-affected regions such as Yemen remain scarce. Aim: To evaluate demographic characteristics, adherence to non-pharmacologic therapy, and antihypertensive prescribing patterns among hypertensive patients attending AL-Thawra Hospital, Sana'a City, Yemen. Materials and Methods: A hospital-based, cross-sectional study was conducted among 120 adult patients with confirmed essential hypertension. Data on demographics, comorbidities, lifestyle adherence, and pharmacological regimens were collected via structured interviews and medical record review. Descriptive statistics and Chi-square tests were used for analysis. Results: Participants were predominantly female (58.3%) and aged 41-70 years (82.5%). Overall, 70% reported adherence to non-pharmacologic recommendations, with consistent rates across comorbidity subgroups. Angiotensin-Converting Enzyme inhibitors/ Angiotensin Receptor Blockers (ACE/ARB) were the most prescribed drug class (61.7%), with significantly higher utilization among females (39.2% vs. 22.5%). ACE/ARB monotherapy was the predominant regimen (39.2%); however, combination therapy with ACE/ARB plus β-blocker was frequently prescribed to patients with heart failure/ischemic heart disease (10.0%), reflecting guideline-aligned practice. Conclusion: Hypertension management in this Yemeni tertiary setting demonstrates reasonable alignment with international guidelines regarding lifestyle counselling and renin angiotensin system inhibitor use. However, underutilization of thiazide diuretics and calcium channel blockers highlights opportunities for protocol optimization. Strengthening drug supply chains and prescriber education may enhance therapeutic outcomes in similar resource constrained environments.
Keywords: Adherence; Antihypertensive therapy; Cross-sectional study; Hypertension; Prescribing patterns; Yemen